Pembebasan Iwadh bagi Istri yang Melakukan Khuluk Terhadap Suami Yang Masih Hutang Mahar: Studi Tekstual Naskah Fath al-Mu‘īn - Willy Zulfan; Muhammad Amar Adly (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Khuluk is a divorce mechanism carried out at the wife's initiative. In Islamic law, the wife is given the right to end the marriage with the burden of providing compensation (iwāḍ) to the husband who is khuluk. New problems arise when the wife performs khuluk against her husband, while the dowry as the wife's right has not been paid by the husband. This article aims to analyze the concept of the wife's release from iwāḍ towards her husband in this condition based on the study of the Fath al-Mu'īn manuscript by Sheikh Zainuddin al-Malibari. This research uses a library method with a normative approach to fiqh and textual analysis. The results show that textual analysis of the Fathul Mu'in manuscript permits the cancellation of the outstanding dowry as a form of compensation (iwāḍ), even opening up the possibility of a full release from iwāḍ. This finding confirms that the obligation of iwadh is conditional and must consider the principles of justice and protection of women's rights in Islamic family law.